COMPOSING MODEL OF DESIGN CRITERIA BASED ON REVEALED PREFERENCE STUDY, BOARDING HOUSES AS DESIGN CASES: MODEL PENYUSUNAN KRITERIA PERANCANGAN BERBASIS STUDI REVEALED PREFERENCES, KASUS DESAIN HUNIAN INDEKOS - Mustakima, Dui Buana; Nurdini, Allis (Universitas Telkom, 2023)
Covid 19 pandemic is a global phenomenon which threatens the safety of people around the world. This phenomenon has become a momentum to reflect back on development in Indonesia. On the other side, the development of boarding houses is going to be massive and mushroomed, because of phenomena of big cities such as work and study. Preference is proper study for revealing tendencies innew normal era. The purpose of this research is to generate design criteria for boarding houses inanew normal era. Method used is revealed preference with hedonic pricing analysis approach adjustedby literature study. The results of programming shows there are eight aspects that should be concernedcarefully; facility, convenience, accessibility, health, sacety and security, cost, service, and quality of visual. These aspects are implied into eight scales; site, public realm, skin, entry, common, unit elements, and mechanical. These scales have 64 factors of designs consist of many principles Keywords : Pandemi Covid 19, Boarding Houses, New Normal.